تقييم الخدمات الانتقالية للطلاب ذوي الإعاقة الفكرية وعلاقتها ببعض المتغيرات من وجهة نظر المعلمين بمدينة جدة - الغبيشي، أسامة أحمد علي; حنفي، علي عبدالنبي محمد (مؤسسة التربية الخاصة والتأهيل, 2024)
هدفت الدراسة الحالية إلى تقييم الخدمات الانتقالية للطلاب ذوي الإعاقة الفكرية من وجهة نظر المعلمين بمدينة جدة، والكشف عن الفروق في تقييم المعلمين لمستوى الخدمات الانتقالية تبعا لمتغير: المرحلة الدراسية، وشدة الإعاقة، والبيئة التعليمية. وبناء عليه تم تصميم استبانة مكونة من (٢٤) عبارة وتطبيقها على (۱۱۱) معلما ممن يعملون في معاهد وبرامج التربية الفكرية بمدينة جدة باستخدام المنهج الوصفي التحليلي. كشفت نتائج الدراسة أن تقييم الخدمات الانتقالية للطلاب ذوي الإعاقة الفكرية جاء بدرجة مرتفعة بمتوسط (٤,٠٣) وبوزن نسبي (٨٠,٥%) من وجهة نظر المعلمين بمدينة جدة، حيث جاء بعد المهارات الاجتماعية في الترتيب الأول، يليه بعد المهارات الأكاديمية، ثم بعد المهارات الاستقلالية وأخيرا بعد التدريب المهني، كما أشارت النتائج عن عدم وجود فروق ذات دلالة إحصائية في تقييم الخدمات الانتقالية تبعا لمتغيرات المرحلة الدراسية وشدة الإعاقة، والبيئة التعليمية، باستثناء بعد المهارات الاستقلالية فتوجد فروق دالة إحصائيا عند مستوى الدلالة (٠,٠٥) لصالح الخدمات الانتقالية للطلاب ذوي الإعاقة الفكرية ببرامج الدمج، وتوصي الدراسة بضرورة التركيز على التدريب المهني في الخدمات الانتقالية المقدمة للطلاب ذوي الإعاقة الفكرية، وضرورة الحرص على تنمية المهارات الاستقلالية للطلاب ذوي الإعاقة الفكرية في معاهد التربية الفكرية. The current study aims at evaluating the transitional services for students with intellectual disabilities from the teachers' point of view in Jeddah, and to reveal the differences in teachers' evaluation of the level of transitional services according to the following variables: educational level, severity of disability, and educational environment. accordingly, a questionnaire consisting of (38) phrases was designed and applied to (111) teachers who work in intellectual education institutes and programs in Jeddah using the descriptive analytical method. The results of the study reveal that the evaluation of transitional services for students with intellectual disabilities came to a high degree with an average (4.03) and a relative weight (80.5%) from the teachers’ point of view in Jeddah, where the social skills dimension came first, followed by the academic skills dimension, then the independence skills dimension and finally vocational training dimension. The results also indicated that there were no statistically significant differences in the evaluation of transitional services according to the variables, educational level, severity of disability, and educational environment, with the exception of the independence skills dimension, where there were statistically significant differences at the significance level (0.05) in favor of transitional services for students with intellectual disabilities in inclusion programs. The study recommends the need to focus on vocational training in the transitional services provided to students with intellectual disabilities, and the need to ensure the development of independence skills for students with intellectual disabilities in intellectual education institutes.
بحث مشتق من رسالة ماجستير بعنوان "تقييم الخدمات الانتقالية للطلاب ذوي الإعاقة الفكرية وعلاقتها ببعض المتغيرات من وجهة نظر المعلمين بمدينة جدة. قسم التربية الخاصة، جامعة أم القرى"
Keywords: ذوي الاحتياجات الخاصة -- الإعاقة العقلية -- الخدمات الانتقالية -- التربية الخاصة -- السعودية